Relacje online. Ekstrawersja i inteligencja emocjonalna w kontekście wybranych aspektów komunikacji internetowej - Bijak, Klaudia; Kleka, Paweł (Człowiek i Społeczeństwo, 2021)
Interpersonal communication is a dynamic, complex process, and is conditioned by many factors, among which one of the most important roles is played by the personality of interaction partners. The article presents results of research on the influence of extraversion and emotional intelligence on selected aspects of communication when the process is mediated by the Internet. The study involved young adults (N = 51) aged 21–27 (M = 24.27; SD = 1.65; Md = 24), mostly women (Nk = 26; K/M = 1.08), who responded to the invitation to the study published on Facebook. The survey was conducted in the period from December 2019 to February 2020, through Messenger and GoogleForms to collect the results in personality questionnaires. On the basis of the correlation coefficients obtained, it can be assumed that the level of extraversion (r = .397, p = .002; r = 414, p < .001 and the level of emotional intelligence (r = .331, p = .009; r = .411, p < .001) may be responsible for the expression of emotions and productivity of the speech in an intermediary conversation. Due to the results of the conducted research, we put forward a thesis that the mediation of contact with another person thanks to the currently developed systems of smileys, does not lead to impoverishment of the emotional layer of the message.